Characterization of a subgroup of non‐type 2 asthma with cow's milk hypersensitivity in young subjects. Issue 1 (22nd February 2019) - Tsolakis, N.; Nordvall, L.; Janson, C.; Rydell, N.; Malinovschi, A.; Alving, K.
Abstract: Background: Asthma with atopy is often characterized by type 2 inflammation but less progress has been made in defining non‐type 2 asthma. We have previously identified a subgroup of young non‐atopic asthmatics with perceived food hypersensitivity and poor asthma control. Objective: Our aim was to further characterize this subgroup of non‐type 2 asthmatics, including the use of a broad panel of inflammation‐related proteins. Methods: Sex‐ and age‐matched subjects (10–35 years old) were divided into three groups with regard to history of asthma and atopy: non‐atopic asthmatics with perceived cow's milk hypersensitivity but with IgE antibodies < 0.35 kUA /L (NAA; n = 24), non‐atopic controls with IgE < 0.35 kUA /L (NAC; n = 24), and atopic asthmatics with IgE ≥ 0.35 kUA /L (AA; n = 29). Serum or plasma were analysed using the multi‐allergen tests Phadiatop and fx5 (ImmunoCAP), a multiplex immunoassay comprising 92 inflammation‐related proteins (Proseek Inflammation), and an ELISA for human neutrophil lipocalin (S‐HNL). Fraction of exhaled nitric oxide (FeNO), blood eosinophil (B‐Eos) count, C‐reactive protein (CRP), airway responsiveness to methacholine (PD20 ), and asthma‐related quality of life (mAQLQ) were also measured. Results: NAA had lower FeNO ( p  < 0.001) and B‐Eos count ( p  < 0.001), but scored worse on mAQLQ ( p  = 0.045) compared with AA. NAA displayed higher levels of matrix metalloproteinase‐1 (MMP‐1) compared with both NAC ( p  = 0.011) and AA ( p  = 0.001), and lower PD20 compared with NAC ( p  < 0.001). In NAA, S‐HNL correlated negatively with PD20 (rho = − 0.048, p  < 0.05) and CRP correlated negatively with mAQLQ (rho = − 0.439, p  < 0.05). Conclusion: In a subgroup of non‐atopic young asthmatics with perceived cow's milk hypersensitivity we observed poor asthma‐related quality of life, airway hyperresponsiveness, and clinically relevant non‐type 2 inflammation. MMP‐1 was elevated in this group, which deserves further studies.